1989
DOI: 10.1007/bf00025391
|View full text |Cite
|
Sign up to set email alerts
|

Identification of indole-3-butyric acid as an endogenous constituent of maize kernels and leaves

Abstract: Indole-3-butyric acid (IBA) was identified by thin layer chromatography, gas-liquid chromatography and gas chromatography-mass spectrometry in kernels and leaves of corn (Zea mays) var . Hazera 224 . Free and ester conjugated IBA were present in dry and germinating corn kernels and leaves . This is the first report of IBA in a monocotyledonous plant and, as far as we know, the first evidence for the presence of conjugated IBA .

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
22
0
1

Year Published

1991
1991
2014
2014

Publication Types

Select...
5
4

Relationship

3
6

Authors

Journals

citations
Cited by 48 publications
(25 citation statements)
references
References 13 publications
2
22
0
1
Order By: Relevance
“…1). The mass spectra ofthe purified and methylated pea extract is consistent with the mass spectra of the methyl ester of IBA obtained by Schneider et al (26) and Epstein et al (12). Highest concentrations of IBA were found in the shoot apex (35.5 ± 4.5 ng/g fresh weight).…”
Section: Gc-mssupporting
confidence: 88%
See 1 more Smart Citation
“…1). The mass spectra ofthe purified and methylated pea extract is consistent with the mass spectra of the methyl ester of IBA obtained by Schneider et al (26) and Epstein et al (12). Highest concentrations of IBA were found in the shoot apex (35.5 ± 4.5 ng/g fresh weight).…”
Section: Gc-mssupporting
confidence: 88%
“…The cytokinins are considered inhibitory (6,7), whereas the auxins are stimulatory (13,21). Although IAA is probably the major auxin, the possibility that other naturally occurring ones like IBA, PAA, 4C1-IAA, and IPA (12,26) participate in regulation cannot be discounted.…”
mentioning
confidence: 99%
“…We incubated 8-dold seedlings in a solution containing 10 mM [ 13 C 8 -15 N 1 ] IBA and assayed levels of [ 13 C 8 -15 N 1 ]IAA after 1 h by using gas chromatography-mass spectrometry (GC-MS) with selective ion monitoring (SIM). We found that wild-type seedlings converted some of the provided IBA to IAA during the 1-h labeling period, demonstrating that Arabidopsis, like other plants (Epstein and Lavee, 1984;Epstein et al, 1989;Epstein and Ludwig-Mü ller, 1993;Ludwig-Mü ller, 2000), can use IBA as an IAA precursor. Moreover, the tir1-1 and axr2-1 auxin-signaling mutants accumulated similar levels of [ 13 C 8 -15 N 1 ]IAA as wild type (Fig.…”
Section: Iba-resistant Mutants Are Defective In Iba-to-iaa Conversionmentioning
confidence: 61%
“…Several studies have demonstrated within the last decade that IBA is present in vascular plants (Epstein et al, 1989;Ludwig-Mü ller andEpstein, 1991, 1993; Ludwig- ). IBA appears to be stored like IAA in a conjugated form with amino acids or sugars , allowing its slow hydrolysis and release.…”
Section: Discussionmentioning
confidence: 99%